Síntese de eninos e enediinos por acoplamento de acetilenos terminais com dicloretos de diorganoil telúrio (IV) - Vargas, Fabricio (2003)
In this work, we have developed an efficient method to prepare enynes and enediynes, by cross-coupling reaction of diorganyl tellurium (IV) dichlorides and terminal alkynes. [...]